Political Interests, Policies and Its Influence To The Patient Satisfaction: A Case Study in Sungai Piring Health Centre, Indragiri Hilir, Riau - Mohammad Suyanto; Arga Christian Sitohang (Political Sciences Program Study, 2024)
Human resources, abbreviated as HR, are potential which are assets and function as non-material or non-financial capital in a business organization which can be transformed into real potential physically or non-physically to realize the success of an organization. One factor that can influence patient satisfaction when visiting a Community Health Center is the quality of service. Service quality is a form of comprehensive and long-term assessment attitude. This research uses comparative casual. The population in this study were patients at the Sungai Piring Riau Community Health Center who had been hospitalized. The population in this study is very large and unlimited (infinite) and the number is unknown to researchers. So the number of research samples was determined using the formula from lamesshow. The results of statistical tests show that service quality has a significant effect on patient satisfaction at the Sungai Piring Indragiri Hilir Community Health Center, Riau Province. Technical skills have a significant effect on patient satisfaction at the Sungai Piring Community Health Center. The results of statistical tests show that the work environment has a significant effect on Patient Satisfaction at the Sungai Piring Community Health Center. The findings in this research has relation to public service. Public service itself will be able to operate very well when there is political interest dan political will that support policy implementation that support service quality improvement in every institution. Political interest and political impetus should has experience a development due to modern era and it involves a spacial perspective.